IL-7-Induced Proliferation of Human Naive CD4 T-Cells Relies on Continued Thymic Activity - Silva, Susana L.; Albuquerque, Adriana S.; Matoso, Paula; Charmeteau-de-Muylder, Bénédicte; Cheynier, Rémi; Ligeiro, Dário; Abecasis, Miguel; Anjos, Rui; Barata, João T.; Victorino, Rui M. M.; Sousa, Ana E. (Frontiers in Immunology, 2017)
Naive CD4 T-cell maintenance is critical for immune competence. We investigated here the fine-tuning of homeostatic mechanisms of the naive compartment to counteract the loss of de novo CD4 T-cell generation. Adults thymectomized in early childhood during corrective cardiac surgery were grouped based on presence or absence of thymopoiesis and compared with age-matched controls. We found that the preservation of the CD31 subset was independent of the thymus and that its size is tightly controlled by peripheral mechanisms, including prolonged cell survival as attested by Bcl-2 levels. Conversely, a significant contraction of the CD31+ naive subset was observed in the absence of thymic activity. This was associated with impaired responses of purified naive CD4 T-cells to IL-7, namely in vitro proliferation and up-regulation of CD31 expression, which likely potentiated the decline in recent thymic emigrants. Additionally, we found no apparent constraint in the differentiation of naive cells into the memory compartment in individuals completely lacking thymic activity despite upregulation of DUSP6, a phosphatase associated with increased TCR threshold. Of note, thymectomized individuals featuring some degree of thymopoiesis were able to preserve the size and diversity of the naive CD4 compartment, further arguing against complete thymectomy in infancy. Overall, our data suggest that robust peripheral mechanisms ensure the homeostasis of CD31 naive CD4 pool and point to the requirement of continuous thymic activity to the maintenance of IL-7–driven homeostatic proliferation of CD31+ naive CD4 T-cells, which is essential to secure T-cell diversity throughout life.